2021
DOI: 10.3390/microorganisms9081659
|View full text |Cite
|
Sign up to set email alerts
|

Microbial L-asparaginase for Application in Acrylamide Mitigation from Food: Current Research Status and Future Perspectives

Abstract: L-asparaginase (E.C.3.5.1.1) hydrolyzes L-asparagine to L-aspartic acid and ammonia, which has been widely applied in the pharmaceutical and food industries. Microbes have advantages for L-asparaginase production, and there are several commercially available forms of L-asparaginase, all of which are derived from microbes. Generally, L-asparaginase has an optimum pH range of 5.0–9.0 and an optimum temperature of between 30 and 60 °C. However, the optimum temperature of L-asparaginase from hyperthermophilic arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 119 publications
(122 reference statements)
0
23
0
8
Order By: Relevance
“…Žilić et al [21] also found that the asparagine content of flours, including blue corn, affected the acrylamide content of biscuits. A related study [31] found that different commercial brands of corn products had wide-ranging amounts of acrylamide (<30-410 µg/kg), suggesting that consumers have a choice of selecting commercial corn-based and other foods with low acrylamide content. These include flatbreads prepared from corn flour as well as almond flour, peanut meal, wheat flour, quinoa flour-peanut meal, wheat flour-spinach, wheat flour-peanut meal-beets, wheat flour-peanut meal-broccoli, yellow corn-wheat tortillas, and wraps ((26.5-56.5 µg/kg, Figure 2) and (3.83-49.1 µg/kg, Figure 3)).…”
Section: Asparagine Content Of Corn Flours and Flatbreadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Žilić et al [21] also found that the asparagine content of flours, including blue corn, affected the acrylamide content of biscuits. A related study [31] found that different commercial brands of corn products had wide-ranging amounts of acrylamide (<30-410 µg/kg), suggesting that consumers have a choice of selecting commercial corn-based and other foods with low acrylamide content. These include flatbreads prepared from corn flour as well as almond flour, peanut meal, wheat flour, quinoa flour-peanut meal, wheat flour-spinach, wheat flour-peanut meal-beets, wheat flour-peanut meal-broccoli, yellow corn-wheat tortillas, and wraps ((26.5-56.5 µg/kg, Figure 2) and (3.83-49.1 µg/kg, Figure 3)).…”
Section: Asparagine Content Of Corn Flours and Flatbreadsmentioning
confidence: 99%
“…Since the levels of asparagine as a proportion of the total free amino acid pool seem to be a key component in acrylamide formation, Muttucumaru et al [32] suggest that plant genetic studies might reduce the asparagine content of plant foods by blocking enzymes involved in its biosynthesis. A complementary approach involves postharvest treatment of plant foods before thermal processing with the enzyme asparaginase, which catalyzes the hydrolysis of asparagine to aspartic acid and ammonia [31]. These promising enzymatic methods merit study with corn and other cereal seeds.…”
Section: Asparagine Content Of Corn Flours and Flatbreadsmentioning
confidence: 99%
“…Type-II enzymes are located in the periplasmic space. They exhibit high specific activity against L-Asn with K M values in two orders of magnitude lower (micromolar K M ) compared to bacterial type I L-ASNases [13].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous research efforts to discover new promising L-ASNases for different fields of biotechnology have turned this group of enzymes into a growing family with amazing diversity. L-ASNases have been isolated from many archaea, bacteria, fungi, and yeast [3,13], and L-ASNases of plant and mammalian origin are now also known [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation